Perilesional white matter integrity in drug-resistant epilepsy related to focal cortical dysplasia. (October 2021) - Jin, Bo; Lv, Zhijun; Chen, Wei; Wang, Chao; Aung, Thandar; Chen, Wenjuan; Wang, Meiping; Wang, Shan; Chen, Cong; Ding, Fang; Geng, Yu; Wang, Shuang
Highlights: We firstly investigated the WM integrity according to drug response in FCD. The WM microstructural abnormalities were different based on AED responsiveness. Drug resistant epilepsy had a more extensive perilesional WM abnormalities pattern. These findings may help to unravel the underlying neuroanatomical character of FCD. Abstract: Purpose: We aimed to investigate the differences of white matter (WM) between the focal cortical dysplasia (FCD) patients with drug-resistant epilepsy and those with drug-responsive epilepsy. Methods: Thirty epileptic patients with MRI-identified or histologically proven FCD were consecutively enrolled. Fractional anisotropy (FA) and mean diffusivity (MD) of the ipsilateral perilesional WM and contralateral homotopic WM layer masks were computed and corrected by the FA/MD of the corresponding hemispheric WM. The difference was evaluated using paired t-tests. The FA, MD and volumes of hemispheric WM and corpus callosum were also calculated. Results: Patients with drug-resistant epilepsy showed significantly decreased FA and increased MD among ipsilateral perilesional WM layer 1 and 2, while patients with drug-responsive epilepsy showed decreased FA in only ipsilateral perilesional WM layer l, compared to remaining ipsilateral perilesional WM layers and contralateral layers 1 through 6. The integrity and volumes of the hemispheric WM and corpus callosum were similar between the two groups. Conclusion: We demonstrated that the WM microstructural alterations differed between epileptic patients with FCD according to their antiepileptic drug responses. More extensive perilesional WM abnormality is observed in patients with drug-resistant epilepsy related to FCD.